If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3w + 4 + -1w + -17 = 0 Reorder the terms: 4 + -17 + -3w + -1w = 0 Combine like terms: 4 + -17 = -13 -13 + -3w + -1w = 0 Combine like terms: -3w + -1w = -4w -13 + -4w = 0 Solving -13 + -4w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -4w = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -4w = 0 + 13 -4w = 0 + 13 Combine like terms: 0 + 13 = 13 -4w = 13 Divide each side by '-4'. w = -3.25 Simplifying w = -3.25
| 6x-1=-3x+13 | | 5(-x+9)-8=-19 | | 72=4x+4(-3x+2) | | -8=-(x+10) | | 6(n+8)=5(n+-4) | | 0.5+6.0y=8.0 | | 8y+4(2+y)=3(y-5)+10y | | 4x+5=-1/3x-8 | | 4x-153=47-6x | | 4/5(x-8)=-12 | | 18=b+3+4b | | x(4x-3)=(4x+6)(x-3) | | (2x-y)(4x^2+2xy+y^2)= | | -32+4x=9x+13 | | 16x+12=93 | | 1/7(x+2)=6 | | -6x-59=3x+121 | | 5x=4(-.33+x)+8 | | 13x+97=-14x+1+15x | | 64s^2-144sf+81f^2= | | 30-5(p-10)=1p | | -23-x=2x+10 | | 5(-6+6x)=-5x+30 | | 3x-(4x+3)=4x-28 | | 5(x+-6)=-5x+30 | | -9x-25=38-6x | | u+2=10 | | 2(2+2x)=3(x-5) | | 9-5x+=4-5x | | -5(x+6)=-5x+30 | | 1+2x-x^2=-6 | | -5(x-6)=-5x+30 |